2014
DOI: 10.1038/labinvest.2013.152
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells markedly suppress inflammatory bone destruction in rats with adjuvant-induced arthritis

Abstract: Mesenchymal stem cells (MSCs) have potential to differentiate into multiple cell lineages. Recently, it was shown that MSCs also have anti-inflammatory and immunomodulatory functions. In this report, we investigated the regulatory function of MSCs in the development of inflammatory bone destruction in rats with adjuvant-induced arthritis (AA rats). MSCs were isolated from rat bone marrow tissues, expanded in the presence of basic FGF, and intraperitoneally injected into AA rats. MSC administration significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 52 publications
1
49
0
1
Order By: Relevance
“…Importantly, it counteracts and overrides angiostatic stimuli, such as those from the CXCL10/CXCR3 axis [49]. CXCL12 also attracts mesenchymal stem cells to the inflammation sites, where they differentiate into osteoblasts and chondrocytes halting inflammatory bone destruction [50]. CXCL12 may decrease in situ inflammation through these highly immunosuppressive mesenchymal stem cells or by direct induction of Th1 repolarization [51, 52].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it counteracts and overrides angiostatic stimuli, such as those from the CXCL10/CXCR3 axis [49]. CXCL12 also attracts mesenchymal stem cells to the inflammation sites, where they differentiate into osteoblasts and chondrocytes halting inflammatory bone destruction [50]. CXCL12 may decrease in situ inflammation through these highly immunosuppressive mesenchymal stem cells or by direct induction of Th1 repolarization [51, 52].…”
Section: Discussionmentioning
confidence: 99%
“…This may contribute to the recruitment of BMSCs to inflammatory sites in vivo. However, Ringe et al reported that human BMSCs did not migrate towards MCP-1 [49] and Takano et al reported similar findings with rat BMSCs [50].…”
Section: Discussionmentioning
confidence: 86%
“…that are taxing to a young healthy individual let alone older individuals [114][115][116]. A preemptive or perioperative administration of MSCs may dampen the immune response, aid in the healing process, and keep at-risk older individuals from declining in functional status (Table 2) [56,[117][118][119][120]. Given the results from the CRATUS, pilot dose finding [55] and randomized placebo controlled study [109] and the number of medical procedures older individuals undergo, large, randomized, double-blinded clinical trials are warranted to elucidate the efficacy of stem cell therapy in regard to the disease process in itself and its ability to suppress the progression of frailty after strenuous medical interventions.…”
Section: Resultsmentioning
confidence: 99%